Influence of phosphate and boron addition to mixed liquid fertilizer on the growth and yield of red chili cultivated in the subsoil layer - Sari, Stefina Liana; Sofyan, Emma Trinurani; Solihin, Eso (Kultivasi, 2024)
This study assesses the impact of adding phosphate and boron in a mixed liquid fertilizer (MLF)  on the growth and yield of red chili plants cultivated in a subsoil environment. The experiment was conducted to comprehend how these nutrients affect the performance of red chili plants, particularly when cultivated in less ideal conditions such as subsoil, a remnant of excavation for brick production. The research was carried out at the Ciparanje Garden of the Faculty of Agriculture, Universitas Padjadjaran. The research design employed a Randomized Completely Block Design with the following treatments: A = Control (degraded soil without fertilizer), B = 0% MLF + 1 NPK, C = 0.25% MLF + 1 NPK, D = 0.50% MLF + 1 NPK, E = 0.75% MLF + 1 NPK, F = 1.00% MLF + 1 NPK, G = 0.5% MLF + 3/4 NPK, H = 0.5% MLF + 1/2 NPK, I = 0.5% MLF + 1/4 NPK, J = 0.5% MLF + 0 NPK, and K = 1 NPK in normal soil. The results revealed that the addition of phosphate and boron in MLF significantly influenced the growth and yield of red chili in subsoil conditions. The recommended MLF concentration was 0.75%, alongside the standard NPK dose. These findings provide crucial insights for the development of more efficient and sustainable agricultural practices, especially in challenging soil conditions like subsoil, where nutrient availability can be a determining factor for agricultural success.